WORDS FROM PICTURES FOR DUAL-CHANNEL PROCESSING. - Dori, Dov (Communications of the ACM, 2008)
The article discusses Object-Process Methodology, which combines graphics and text representations of complex systems to make it easier to understand technical ideas in computer programming. The author argues on behalf of the Object-Process Methodology approach in addressing assumptions about the dual channel and active processing. Bimodality and complexity management via hierarchical decomposition is demonstrated, and the author details ways to employ some of the ideas in the article in the Systems Modeling Language.